Impacts of conditional cash transfers on fish consumption: Evidence from Tanzania - Montanio, Kyle; Uchida, Emi; Kosec, Katrina (University of Chicago Press, 2023)
Poverty reduction and conservation of natural resources are both global goals for sustainable development. However, it is not well understood how interventions to reduce poverty impact coastal communities and the fisheries they depend upon. This study explores the impact of a conditional cash transfer (CCT) program in Tanzania on local fish consumption decisions. To overcome the endogeneity of poverty to dependence on fisheries, we exploit a randomized controlled trial implemented in the initial rollout of the CCT. We allow for heterogeneous impacts based on initial household wealth and find that CCT participation increases demand for the poorest households in our study. We also differentiate by types of fish and find that dagaa—a low-value fish common in Tanzania—is primarily driving changes in fish consumption.